(3GdeZGQI GdehMTIs - (3SfjcJ, djehfjs; (3TQa, eMehOs; (3YHO Gddg, QTGs; (3jS, CSeGAs ((3GdbGgQIs (3eQcR GdeMQhSI ddfTQs, 2024)
(3YRjRj GdbGQF(B.. (3eG de Jcf OhOI QNhnqjI, Ch TbGFb fYeGf HMQjI, Ch nYnakfG aWQkqjG, aQHeG dG JapqVd GdQWhHI, hbO dG JapqVd cPdc bQGAI gPG GdcJGH; EP jhGLg GdCNhI HhOdjQ cpqenqjkI oeRpYLI ddZGjI ef GdQWhHI aj QMdI fRhdge Edi CYeGb GdjCS JMJ GdeGA(B. (3aj GdMbjbI jhGLghf GdcKjQ LkqOG ef GdaXGFY GdJj dG jecf MUQgG, hCfJ dG JQjOfj WHkYG Cf CPcQ CShCgG, GdPj jJVnqef GdoaWQ, hGdHMK GdjGFS Yf TjA eabhO, hhMT ejcGfjcj, hQSGdI eRYLI ef UOjb eabhO, hQbUI cdGcjJ(B. (3hHGYJHGQj eDpqdkaG eJaGfkjG JYnqgO HJOhjf bUI GdCNhI HhOdjQ GdHGFSI; Ydnqj Cf CSJeQ aj GdZhU aj Yeb CYeGb MjGI GdCjJGe(B. (3CnqeG CfnJ, aQHeG Ydjc Cf JJYnqeb aj bQGAI cJGH CcKQ eQkMG cj JMGaX Ydi Yjfjc, hYdi eYfhjGJc ef GdGfgjGQ(B. (3eY cGed GMJQGejs
(3GdbUU GdeJQLeIs
1 2
Keywords: (3GdeJQLeGJs